Impact of coronavirus disease-2019 pandemic on Hemodialysis care delivery pattern in Karnataka, India: A Cross-sectional, questionnaire-based survey - Y J Anupama; Arvind Conjeevaram; A Ravindra Prabhu; Manjunath Doshetty; Sanjay Srinivasa; Venkatesh Moger (Wolters Kluwer Medknow Publications, 2021)
Background: The coronavirus disease-2019 (COVID-19) pandemic has disrupted health-care delivery globally. Patients on in-center hemodialysis (HD) are particularly affected due to their multiple hospital visits and the need for uninterrupted care for their well-being and survival. We studied the impact of the pandemic and the national policy for pandemic control on the HD care delivery in Karnataka state in India in April 2020, when the first and second national lockdown were in place. Materials and Methods: An online, questionnaire-based survey of dialysis facilities was conducted, and the responses analyzed. The questions were pertaining to the key areas such as changes in a number of dialysis treatments, frequency, duration, expenses, transportation to and from dialysis units, impact on the availability of consumables, the effect on dialysis personnel, and on machine maintenance. Results: Sixty-two centers participated. Median of dialysis treatments for the months of March and April 2020 was 695.5 and 650, respectively. Reduction in dialysis treatments was noted in 29 (46.8%) facilities, decreased frequency reported by sixty centers. In at least 35 (56.5%) centers, dialysis patients had to bear increased expenses. Cost and availability of dialysis consumables were affected in 40 (64.5%) and 55 (88.7%) centers, respectively. Problems with transportation and movement restriction were the two key factors affecting both patients and dialysis facilities. Conclusions: This survey documents the collateral impact of COVID-19 on the vulnerable group of patients on HD, even when not affected by COVID. It identifies the key areas of challenges faced by the patients and the facilities and implores the care providers for finding newer avenues for mitigation of the problems.